Evaluating the effectiveness of a nutrition-sensitive agriculture intervention in Western Kenya: design of the Mama SASHA cohort study of vitamin A. - Girard, Amy W.; Grant, F.; Okuku, H.S.; Akelo, V.; Wanjala, R.; Levin, C.; Cole, D.; Low, Jan W. (2014)
The 2013 Lancet Maternal and Child Nutrition series identified evaluations of nutrition-sensitive agricultural interventions as a research priority. The Mama SASHA study in Western Kenya links delivery of vitamin A (VA) rich orange-flesh sweet potato (OFSP) to antenatal care to improve VA and nutritional status of pregnant and lactating women and their children. The evaluation strategy includes a nested longitudinal study following women and their infants from pregnancy to 9 months postpartum. VA status is assessed using infection-adjusted plasma retinol binding protein and breastmilk retinol (postpartum). Maternal and child infection, iron, and anemia status, anthropometry, diet, health services uptake, and food security status are also measured. 505 eligible pregnant women, attending ANC at 4 control and 4 intervention facilities, were consented and enrolled. At enrollment women in control and intervention communities did not differ with respect to VA, iron, anemia or anthropometric status; food security or dietary diversity scores; demographic characteristics; awareness of vitamin A; or consumption of vitamin A rich foods in the past 7 days. Only 10 women consumed OFSP in the previous 7 days; all in intervention communities. The longitudinal study will contribute to rigorous evaluation of the OFSP intervention on maternal and child VA status and allow assessment of program impact pathways.